Old Blood, Bad Blood, and Youngblood: Due Process, Lost Evidence, and the Limits of Bad Faith - Norman C. Bay (Washington University Law Review, 2008)
Under the law of lost evidence, absent a showing of bad faith, no due process violation occurs when the police lose potentially exculpatory evidence. This is so even though the evidence may be critical to the defense and even though post-conviction DNA testing has exonerated more than 200 individuals. Ironically, the case that developed that rule of law, Arizona v. Youngblood, is founded on the conviction of an innocent man. This Article critically examines Youngblood and provides a conceptual framework for examining the constitutional right of access to evidence. Supreme Court precedent reflects two different, sometimes competing, visions of procedural due process: adjudicative fairness to the accused or an instrumental focus on deterring official misconduct. In Youngblood, instrumentalism trumped adjudicative fairness. Moreover, four compelling developments in the twenty-one years since Youngblood was decided scientific advances, legislative reform, state judicial disapproval, and doctrinal incoherence have eroded its rationale and legitimacy. For all those reasons, Youngblood no longer merits stare decisis effect and should be overruled. In its place, the-Court should apply an approach that takes into account the nature of the government's conduct and the degree of prejudice suffered by the accused. This approach restores balance to the constitutional right of access to evidence; it encompasses a broader vision of due process that promotes adjudicative fairness. In some cases, the loss of potentially exculpatory evidence ought to result in a due process violation, even in the absence of bad faith.
Keywords: Due process of law; Actual innocence; Evidence (Law); Bad faith (Law); Arizone v. Youngblood